Reliability and Construct Validity of the Health-Promoting Lifestyle Profile II in an Adult Turkish Population - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
Background: Little is known about health-promoting lifestyle behaviors among Turkish people, who are experiencing a lifestyle transition from a developing country to one undergoing rapid modernization, although health promotion is receiving increasing attention regarding its prominent role in healthcare. Use of the Health-Promoting Lifestyle Profile II (HPLPII) has the advantage of allowing comparison of different international populations, although cultural adaptations are needed. Objectives: The aims of this study were to adapt the HPLPII culturally and to assess its psychometric properties. Methods: Analyzed were internal reliability among 972 adults and test-retest stability among 160 adults. Construct validity was evaluated by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Samples sizes for EFA and CFA were 420 and 500, respectively. Results: Cronbach's alpha coefficients surpassed .70 for HPLPII and six subscales. All items, except one, had acceptable item-total correlations of >.20. Test-retest results showed stability for HPLPII and for subscales. Varimax rotation yielded five factors with eigenvalues >1, explaining 41% of the variance. Two items were excluded because their factor loadings differed by <.30 or they had cross-factor loadings. The CFA five-factor model based on EFA represented an acceptable fit. Testing of latent construct measurement models reduced the number of items from 52 to 48. The revised 48-item six-factor model had perfect fit. Discussion: The HPLPII had satisfactory psychometric properties. It can be used to measure health-promoting lifestyle in the Turkish population.
Keywords: construct validity; HPLPII; reliability; Turkish people; LANGUAGE